Middle European Scientific Bulletin, VOLUME 11 April 2021 Activities and Financial Status of Bukhara Mangit Rulers in The Years Of Independence: Middle European Scientific Bulletin, VOLUME 11 April 2021 Activities and Financial Status of Bukhara Mangit Rulers in The Years Of Independence - To'rayeva, Guli (Центр Научных Публикаций (buxdu.uz), 2021)
In this article, articles on the personality and socio-political activities of the rulers of Mangit in Bukhara, the financial and economic situation, the source significance of the periodicals of independence have been scientifically studied and analyzed on a new methodological basis.